Research news - Muzamir, Hasan (Kolej Kejuruteraan, 2020)
Hokoku Engineering of Japan has awarded an international grant of RM 50,000 to Assoc Prof Ts Dr Muzamir Hasan from the Department of Civil Engineering for a project entitled “Development of IoT Geotechnical Data Mapping System for Pahang”.